Jewelry-theft in the Pécs cathedral (Academic Journal of Internal Affairs, 2018)
The author provides an overview of the investigation concerning the theft of 18–19th century jewelry from the Cathedral of Pécs, Hungary.
Keywords: investigation; jewelry-theft; cathedral